The association of COVID-19 occurrence and severity with the use of angiotensin converting enzyme inhibitors or angiotensin-II receptor blockers in patients with hypertension. - Mingfei Li; Ying Wang; Ndindam Ndiwane; Michelle B Orner; Natalia Palacios; Brant Mittler; Dan Berlowitz; Lewis E Kazis; Weiming Xia (PLoS ONE)
Background A number of studies have reported the association between the use of angiotensin-converting enzyme inhibitor (ACEI) and angiotensin-II receptor blocker (ARB) medications and the occurrence or severity of coronavirus disease 2019 (COVID-19). Published results are inconclusive, possibly due to differences in participant comorbidities and sociodemographic backgrounds. Since ACEI and ARB are frequently used anti-hypertension medications, we aim to determine whether the use of ACEI and ARB is associated with the occurrence and severity of COVID-19 in a large study of US Veterans with hypertension. Methods Data were collected from the Department of Veterans Affairs (VA) National Corporate Data Warehouse (VA-COVID-19 Shared Data Resource) between February 28, 2020 and August 18, 2020. Using data from 228,722 Veterans with a history of hypertension who received COVID-19 testing at the VA, we investigated whether the use of ACEI or ARB over the two years prior to the index date was associated with increased odds of (1) a positive COVID-19 test, and (2) a severe outcome (hospitalization, mortality, and use of intensive care unit (ICU) and/or mechanical ventilation) among COVID-19-positive patients. We used logistic regression with and without propensity score weighting (PSW) to estimate the odds ratio (OR) and 95% confidence interval (95% CI) for the association between ACEI/ARB use and a positive COVID-19 test result. The association between medication use and COVID-19 outcome severity was examined using multinomial logistic regression comparing participants who were not hospitalized to participants who were hospitalized, were admitted to the ICU, used a mechanical ventilator, or died. All models were adjusted for relevant covariates, including demographics (age, sex, race, ethnicity), selected comorbidities, and the Charlson Comorbidity Index (CCI). Results The use of ACEI significantly decreased the odds of a positive COVID-19 test among Veterans with hypertension (OR = 0.917, (0.887, 0.948) and OR = 0.926, (0.894, 0.958) with PSW). The use of ACEI, but not of ARB, was also associated with significantly increased odds of using mechanical ventilators (OR = 1.265, (1.010, 1.584) and OR = 1.210, (1.053, 1.39) with PSW) among all COVID-19 inpatients compared to outpatients. Conclusions In this study of Veterans with hypertension, ACEI was significantly associated with decreased odds of testing positive for COVID-19. With the exception of the association of ACEI with a small non-clinically-important increase in the odds of using mechanical ventilators, neither ACEI nor ARB was found to be associated with clinical severity or mortality among COVID-19-positive Veterans. The results of this study need further corroboration and validation in other cohort samples outside the VA.